2010
DOI: 10.1111/j.1365-3016.2010.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Living near agricultural pesticide applications and the risk of adverse reproductive outcomes: a review of the literature

Abstract: Objectives This systematic review evaluates the current epidemiological evidence on the association between living near agricultural pesticide applications and adverse reproductive outcomes, including congenital malformations, stillbirth, intrauterine growth retardation (IUGR), low birthweight, preterm birth and spontaneous abortions. Methods We identified and reviewed 25 studies from a systematic search of the main scientific databases and other sources published in 1950 to 2007. Study methods and main result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 100 publications
(262 reference statements)
1
32
1
Order By: Relevance
“…Shirangi et al, [43] in a systematic review of the literature, assessed the current epidemiological evidence of the association between residents of nearby areas with application of pesticides in agriculture and adverse reproductive outcomes, including congenital malformations. They concluded that the scientific evidence suggests an association with congenital malformations; however, due to methodological limitations of the various studies, a definitive conclusion was not reached.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Shirangi et al, [43] in a systematic review of the literature, assessed the current epidemiological evidence of the association between residents of nearby areas with application of pesticides in agriculture and adverse reproductive outcomes, including congenital malformations. They concluded that the scientific evidence suggests an association with congenital malformations; however, due to methodological limitations of the various studies, a definitive conclusion was not reached.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Methodological shortcomings with respect to establish an exposure-response relationship, to control confounding factors and assess large populations represent the challenges to be overcome by future researches. [43] Fogh-Andersen [44] first defined genetic factors as etiological factors of cleft lip and palate, which was later confirmed by segregation analysis. Since then, a variety of genetic approaches has been used to identify genes and loci involved in the etiology of clefts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the outcomes, the congenital malformations had presented a strong force of association. Other outcomes like low birth weight (LBW), prematurity and abortion, while presenting weaker associations, deserve new inquiries 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Dear Sir, An analytical observational study by Cremonese et al 1 recently suggested that prenatal exposure to pesticides is a risk factor for poor pregnancy outcomes such as pre-term births and lower Apgar scores. The authors used an ecological (correlational) study to investigate whether there was an association between exposure to pesticides (in general) and poor pregnancy outcomes in micro-regions of states in the South Region of Brazil.…”
mentioning
confidence: 99%
“…Using the MEDLINE databank, a search with the keywords "pesticide" and "pregnancy", yields 4,122 publications, the first of which dates back to 1937. In this sense, although the interest on the effects of such chemicals during pregnancy is old, the establishment of an accurate exposure assessment presents several difficulties 1 .…”
mentioning
confidence: 99%